The implementation of the democratic regime in Eastern Europe The way in which the type of democracy in the case of the Republic of Moldova affects its credibility as an international actor (1990-2015) - Vidrașcu, Olimpiada (2016)
Dissertação de Mestrado em Relações Internacionais